PENGEMBANGAN PERANGKAT PEMBELAJARAN MATEMATIKA BERBASIS PROBLEM BASED LEARNING PADA MATERI HIMPUNAN UNTUK SISWA KELAS VII SMP/MTs - Indah Fitriani Fitriani; Armis '; Sehatta Saragih (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The background of this study is the limited of mathematics learning documents as supporting learning referring to 2013 Curriculum. This study aimed to develop mathematics learning documents with problem based learning’s model on set  for 7th grade SMP/MTs. Learning instruments in this study are lesson plans, and student worksheet. This study method used is 4D model by Thiagarajan that consist of define, design, development, and disseminate, but the study was only to development step. Based on the data analysis, it can be conclude that mathematics learning documents is very valid with mean validity of lesson plans is 3,62, and mean validity of student worksheet is 3,53. This student worksheet has also reached the practical qualification with mean percentage of student responses is 96,67% on a small test group.